Variations in α-, β-amylase and α-glycosidase activities in two genotypes of wheat under NaCl salinity stress - Chiraz, Chaffei Haouari; Afef, Hajjaji Nasraoui; Donia, Bouthour; Houda, Gouia (Plant Breeding and Seed Science, 2012)
Two wheat differing in salt sensitivity, was examined for osmolyte contents and activities of α-amylase, β-amylase and α-glucosidase enzymes involved in seeds germination, in absence as well as in presence of 100, 150, 200 and 300 mM NaCl. The inhibitory effects of NaCl differed, depending on the species tested. In wild wheat specie (Triticum monococcum), with reduced germination percentage and lower relative water content, the increase in NaCl concentration resulted in the decrease in endogenous level of proline, total soluble sugars and activities of the main enzymes involved in the germination process. In contrast, cultivated wheat specie (Triticum aestivum) seed in response to salt stress accumulated higher proline and total soluble carbohydrate concentrations which improved their water status and the enzyme activities involved in the germination process. Differential response of the different species of wheat to salt stress is governed by the accumulation of osmolytes in seeds.